FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS MUARA BATU KECAMATAN MUARA BATU KABUPATEN ACEH UTARA - Munika Aruna; Cut Sriyanti; Aida Fitriani; Erlina Erlina; Hendrika Wijaya Kartini Putri (PT. Intelek Cendikiawan Nusantara, 2026)
Background back : In general problem nutrition Still experience improvement from year to year . Nutrition bad is reason death highest children in the country develop . Approximately 870 million people out of 7.1 billion resident world or 1 of eight residents​ world suffer nutrition bad And part big live in the country develop . Objective Research : Objectives study This that is For know factors that influence nutritional status toddlers in the Work Area Community Health Center Estuary Rock Subdistrict Estuary Rock North Aceh Regency in 2025. Method Research : Design research used​ is study cross-sectional analysis. Population in study This that is mother who has toddler a number of 1,792 people . Sample taken with random sampling technique of 95 respondents . Results Research : Based on results study show that majority respondents own knowledge less (38.9 % ), income family majority below the UMP (72.6%), the majority No give immunization complete (82.1%), majority No provide breast milk exclusive (82.1%) and nutritional status in category good /normal (87.4%). From the results test Chi-square show p -value ( 0.025 ), while For variables attitude show p -value (0.006), immunization status variable show p -value (0.224), and variables breastfeeding shows​ p -value (0.000). Conclusion : From the results study can concluded There is influence knowledge on nutritional status toddler p -value (0.025), there is influence attitude on nutritional status toddler p -value (0.006), no There is influence of immunization status on nutritional status toddler p -value (0.224), and There is influence breastfeeding on nutritional status​ toddler p -value (0.000). Suggestion: Share respondents Can become material input as well as material evaluation about nutritional status toddlers . Keywords : Knowledge , Income , Immunization Status , History Breastfeeding , Nutritional Status Toddler